Expansion and application of dye tracers for measuring solid food intake and food preference in Drosophila - Brandon C. Shell (Nature Portfolio, 2021)
Abstract The Drosophila model is used to investigate the effects of diet on physiology as well as the effects of genetic pathways, neural systems and environment on feeding behavior. We previously showed that Blue 1 works well as a dye tracer to track consumption of agar-based media in Drosophila in a method called Con-Ex. Here, we describe Orange 4 as a novel dye for use in Con-Ex studies that expands the utility of this method. Con-Ex experiments using Orange 4 detect the predicted effects of starvation, mating status, strain, and sex on feeding behavior in flies. Orange 4 is consumed and excreted into vials linearly with time in Con-Ex experiments, the number of replicates required to detect differences between groups when using Orange 4 is comparable to that for Blue 1, and excretion of the dye reflects the volume of consumed dye. In food preference studies using Orange 4 and Blue 1 as a dye pair, flies decreased their intake of food laced with the aversive tastants caffeine and NaCl as determined using Con-Ex or a more recently described modification called EX-Q. Our results indicate that Orange 4 is suitable for Con-Ex experiments, has comparable utility to Blue 1 in Con-Ex studies, and can be paired with Blue 1 to assess food preference via both Con-Ex and EX-Q.